Learning Strategy Oriented to High Order Thinking Skills (HOTS) - Kurniawan, Andriyanto; Wahyuni, Sri; Sugiyatmi, Anik; Pratiwi, Veronika Unun; Nugrahani, Farida (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
The aim of the research is to describe High Order Thinking Skills-oriented Indonesian language learning strategies in learning at school. The research method used is qualitative. The approach in this research is descriptive qualitative. The data used is in the form of various learning strategies in the independent curriculum related to the implementation of Indonesian language learning activities in schools. Data sources were obtained through scientific articles and journals which theoretically have been proven to be relevant regarding the relevance of using HOTS (High Order Thinking Skill) oriented Indonesian language learning strategies. Data collection techniques use library research. Data analysis techniques use reading, listening and taking notes. Data validity techniques through theoretical triangulation. The research results show that (1) Indonesian language learning strategies are oriented towards high level thinking including project based learning, problem based learning, discovery learning, and inquiry. (2) learning Indonesian using the project based learning model will make students active, creative and innovative in producing learning products. (3) The use of the problem based learning model in Indonesian language learning makes students trained to formulate and solve problems carefully so that independent activities and constructive thinking can be mastered by students. The use of discovery learning and inquiry models makes students more skilled in critical thinking to find new ideas and understanding in learning Indonesian. The criteria for learning strategies oriented at a high level of thinking are based on the 4Cs as characteristics of 21st century learning.